CONVERSATIONAL IMPLICATURE IN MATA NAJWA’S TALK SHOW - Swarman Rindu M. Siahaan and Muhammad Natsir (LINGUISTICA, 2015)
The objectives of this research were to find out the two types of conversationalimplicature, they are; generalized conversational implicature and particularizedconversational implicature and to describe the reason of the most dominant typeof conversational implicature. This research was conducted by using descriptivequalitative. The data was collected by applying documentary technique such as;collecting reference and journal related to the study, searching and selecting thesource of data, downloading the data from youtube, and transcribing the script ofthe show. The data were taken from six segments of one episode of Mata Najwa’stalk show. The two types of conversational implicature were occurred in theepisode of Mata Najwa’s talk show. The findings of data analysis showed that thetotal numbes of conversational implicature was 84 occurrences. The two typeswere Generalized Conversational Implicature 49 (58.33%) and ParticularizedConversational Implicature 35 (41.67%). The most dominant type ofconversational implicature was Generalized Conversational Implicature. It showsthat the interviews usually used the clear, brief and straightforward statements inorder to avoid the ambiguity and to make the listeners were able to understandwhat he/she said. And also this program is expected to give information,interested and give some positive lessons to the listeners.